Mengembangkan Penjualan UMKM Alby Key dengan Web E-Commerce - Mardiani, Eri; Fachri,; Suhatmojo, Guing Tri; Nurfaizi, Kelfin; Perdana, Muhammad Rizky; Putro, Prayogo Dwi Cahyo; Dhema, Salestinus Petrus; Prasetyo, Yoga Dwi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
During the pandemic, people are exposed to the risks of in-person trading and tend to switch to digital trading. The purpose of this study is to examine the development of micro, small and medium enterprises (MSMEs) using the waterfall method. The data shows that online sales and purchases have increased significantly, prompting businesses to adopt digital distribution systems. The research highlights the need for community creativity, especially to reduce direct transactions and increase revenues through Internet platforms. In business settings, e-commerce acts as an intermediary for online transactions. Develop online sales and provide features that help buyers improve customer satisfaction and overall sales. The study provides a systematic and sequential overview of how MSMEs are evolving in meeting the challenges of the pandemic, highlighting the importance of adaptation and innovation in digitally enabled trading to business success.
Keywords: Sale; Web; MSME; E-Commerce